Critical skating intensity on a slide board: physiological and neuromuscular responses and correlation with performance on ice - Piucco, T.; Phillips, J.; Finnie, J.; Rados, A.; Dantas de Lucas, R. (Applied Physiology, Nutrition, and Metabolism, 2019)
The aim of this study was to assess the physiological and neuromuscular responses at critical skating intensity on a slide board and to investigate the correlations between critical cadence (CC) and skating performances on ice. Thirteen well-trained speed skaters (age,19.8 ± 4.2 years; weight, 69.6 ± 9.06 kg) performed a maximal skating incremental test (IT) on a slide board. CC was determined from 3 to 4 trials to exhaustion lasting from 3.1 ± 0.7 to 13.9 ± 3.1 min, using linear and hyperbolic mathematical fittings. A time to exhaustion test at CC (TTE-CC) was performed. CC values (55.3 ± 5.0 ppm) were significantly higher than cadence at the respiratory compensation point (RCP) (53.5 ± 4.0 ppm). Mean duration of TTE-CC was 22.9 ± 4.8 min. Peak values of oxygen uptake, heart rate (HR), ventilation, respiratory exchange ratio (RER), and ratings of perceived exertion (RPE) during TTE-CC were significantly lower (p < 0.05) than the peak values reached during the IT. Oxygen uptake, HR, ventilation, RER, and RPE significantly increased from 25% to 100% of TTE-CC. Muscle activity (integrated electromyography) significantly increased after 75% of TTE-CC for vastus lateralis and gluteus maximus muscles. Oxygen uptake at CC was better associated to skating performance on 500, 1000, 1500, and 5000 m than peak oxygen uptake at IT and oxygen uptake at RCP. Physiological responses indicate that critical skating intensity on slide board occurred within the heavy exercise domain where oxygen uptake increases but does not reach its maximum. Critical cadence could be used as a better indicator of performance and training prescription for long track speed skating distances.